2020
DOI: 10.1109/access.2020.2989330
|View full text |Cite
|
Sign up to set email alerts
|

Flagging Implausible Inspection Reports of Distribution Transformers via Anomaly Detection

Abstract: Distribution transformer is the key equipment in the distribution power grid, and sampling inspection is the main method used to ensure quality control. Inspection comprises many testing processes. Due to various reasons, the testing results may occasionally have errors and be implausible. Only a few errors can be detected empirically by inspectors. To solve this problem, anomaly detection is proposed in this paper to determine implausible inspection reports and assist in re-inspecting. The well-known and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The identification of the busduct overheating fault is essentially a two-classification problem in machine learning, that is, identifying the normal state and overheating state. In recent years, many classification algorithms have emerged in machine learning (Xiang et al, 2020), such as KNN (K-nearest neighbor) (Cover and Hart, 1967), SVM (support vector machine) (Schölkopf and Smola, 2002), Naive Bayes (Murphy, 2006), decision tree (Quinlan, 1986), random forest (Breiman, 2001), and AdaBoost (Freund and Schapire, 1995). Among them, AdaBoost has been proven to be extremely successful in generating accurate classifiers, especially, applied to two-classification problems (Zhu et al, 2009).…”
Section: Adaboost Classifier For Overheating Identificationmentioning
confidence: 99%
“…The identification of the busduct overheating fault is essentially a two-classification problem in machine learning, that is, identifying the normal state and overheating state. In recent years, many classification algorithms have emerged in machine learning (Xiang et al, 2020), such as KNN (K-nearest neighbor) (Cover and Hart, 1967), SVM (support vector machine) (Schölkopf and Smola, 2002), Naive Bayes (Murphy, 2006), decision tree (Quinlan, 1986), random forest (Breiman, 2001), and AdaBoost (Freund and Schapire, 1995). Among them, AdaBoost has been proven to be extremely successful in generating accurate classifiers, especially, applied to two-classification problems (Zhu et al, 2009).…”
Section: Adaboost Classifier For Overheating Identificationmentioning
confidence: 99%
“…The identification of the busduct overheating fault is essentially a two-classification problem in machine learning, that is, identifying the normal state and overheating state. In recent years, many classification algorithms have emerged in machine learning (Xiang et al, 2020), such as KNN (K-nearest neighbor) (Cover and Hart, 1967), SVM (support vector machine) (Schölkopf and Smola, 2002), Naive Bayes (Murphy, 2006), decision tree (Quinlan, 1986), random forest , and AdaBoost (Freund and Schapire, 1995). Among them, AdaBoost has been proven to be extremely successful in generating accurate classifiers, especially, applied to two-classification problems (Zhu et al, 2009).…”
Section: Adaboost Classifier For Overheating Identificationmentioning
confidence: 99%
“…Because the amount of current data is huge, we argue that current anomaly detection requires a scalable system architecture ability including real-time data processing, resource efficiency, fault tolerance, and extensibility. Xiang et al [ 5 ] identified abnormal samples in distribution transformer inspection reports, assisted inspectors to complete inspection work correctly and efficiently. Balouji et al [ 6 ] integrated an advanced generative adversarial network to detect anomalies in FDIA data.…”
Section: Introductionmentioning
confidence: 99%